2015
DOI: 10.1097/ta.0000000000000725
|View full text |Cite
|
Sign up to set email alerts
|

Delayed intracranial hemorrhage in the anticoagulated patient

Abstract: Systematic review, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…The mortality was similar for TBI between the medication groups. A recent systematic review and meta‐analysis have found, for warfarin, the risk of delayed intracranial hemorrhage (ICH) was low in minor head injury, and there was no increased risk of death for antiplatelet agents . These findings are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…The mortality was similar for TBI between the medication groups. A recent systematic review and meta‐analysis have found, for warfarin, the risk of delayed intracranial hemorrhage (ICH) was low in minor head injury, and there was no increased risk of death for antiplatelet agents . These findings are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…This would be expected when anticoagulant therapy increases the hemorrhagic risk in itself, although head trauma can also promote trauma-induced coagulopathy and, consequently, ICH [ 35 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low rates of DICH and even lower rates of subsequent neurosurgical operative intervention have caused many to question the value of the routine repeat head CT [ 19 ]. Yet, others still see it as a valuable tool to diagnose DICH, especially since there are no known predictors of DICH [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%